The Difference of Effectiveness of Ginger Warm Compress and Consumption of Acidic Turmeric on Decreasing Primary Menstrual Pain Scale - Ria, Matilda Bupu; Ola, Clara Yunita Ina; Palalangan, Damita (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Dysmenorrhoea is pain during menstruation that is felt by teenage women, usually they experience cramps and are concentrated in the lower abdomen. Complaints of menstrual pain can vary, ranging from mild to severe. The purpose of this study was to analyze the difference in the effectiveness of ginger warm compresses and the consumption of tamarind turmeric on reducing the primary menstrual pain scale.Subjects and Method: This study was conducted using a quasi-experimental type two group pre post test design, with a population of all female students who experienced primary menstrual pain and a sample of 30 respondents with warm ginger compresses and 30 respondents who consumed tamarind and turmeric drinks. The sample was collected by purposive sampling. The data were collected by questionnaire. The independent variable was warm compresses of ginger and consumption of tamarind turmeric, the dependent variable was primary menstrual pain. The analysis used was the Wilcoxon and Mann Whitney tests.Results:Based on the results of the Wilcoxon test, there was an effect of giving a warm ginger compress (p= 0.004). Likewise, giving tamarind turmeric drink showed an effect with the result p<0.001. Based on the results of the Mann Whitney test, there was a significant difference in the effectiveness of ginger warm compresses and the consumption of tamarind turmeric on reducing the primary menstrual pain scale, with p = <0.001 results.Conclusion: It is hoped that respondents, readers, further researchers, and especially young women who experience menstrual pain, consume tamarind regularly in dealing with primary menstrual pain complaints as a non-pharmacological therapy.Keywords: primary menstrual pain, warm compresses of ginger, consumption of tamarind turmeric.Correspondence: